The future of evaluation: prospects and challenges - Stockmann, Reinhard (2014)
It is not possible to predict the future of evaluation. However, some well-founded assumptions can be made as to how evaluation is likely to develop on the basis of the current situation and the processes of social change in the future. First, a series of indicators is used to show that evaluation is in a historic growth phase. After formulating three social functions of evaluations, it is ascertained that the extent to which these functions have been institutionalized varies considerably. Most governmental and non-governmental organizations have firmly established evaluation as a management function. As an instrument of management in democratic governance, evaluation is less strongly institutionalized. The weakest institutionalized structures are to be found when it comes to the enlightenment function. What are needed here, above all, are independent institutions with their own budget, which could operate freely without administrative constraints and agendas. The final part of the article focuses on the challenges and dangers that evaluation must respond to if the importance of the three functions of evaluation is to be increased rather than allowed to decline.